Analysis of volatile compounds in roasted Liberica Coffee in the Philippines by gas chromatography mass spectrometry (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2024)
In the Philippines, not much research has been accessible for the volatile compounds of roasted Liberica coffee. Thus, these findings might contribute to the addition of preliminary data for the said coffee variety. The research sought to provide information regarding the volatile compounds of roasted Liberica coffee (Coffea liberica) collected from Lipa Batangas in the Philippines. Sample analysis was performed using Static Headspace Gas Chromatography. The roasting process generated furans, pyridines, aldehydes, and pyrazines potent volatile compounds in Liberica beans including unique volatile compounds including terpinene 4-acetate (0.65%) and trans--Ocimene (0.47%). Furthermore, the presence of the abovementioned compounds revealed the essential marker as Liberica coffee beans.